Commemorative tourism: Menuju sebuah tipologi daya tarik wisata yang berhubungan dengan kematian dan bencana - Kasih Cakaputra Komsary (Program Studi Hospitality dan Pariwisata, 2017)
Tourism from time to time continues to change in terms of typology based on the characteristics of tourist attraction and motivation. One of the typology used is dark tourism that linking tourist attraction with death and disaster. The tragedy that occurred in the past were likely to cause death, especially in mass quantities, the death of famous persons, public figures often stimulate a person to travel. Activities undertaken during this much more about remembering and honoring the death and catastrophic events that have occurred. But actually, if it is viewed from the supply side, the attraction being visited is not new and the term dark tourism gives the impression as if the tourist activity conducted in conjunction with real events associated with death and disaster. Although tourist activities is not necessarily related to real events that deal directly with tourists, but it is more influenced by the tourist motivation to do homage to the deceased and as self- reflection to see the events or tragedies in the past as a consideration in living in the present. This paper tries to offer a term in the typology of tourist attraction with a positive meaning: the commemorative tourism. Keywords: dark-tourism, heritage, commemorative